Photo-enhanced conduction in inhomogeneous thin film space charge limited conducting systems. - Bąk, Grzegorz W. (Wydawnictwo Politechniki Łódzkiej, 2016)
Photo-enhancement of space-charge limited currents in deliberately modified thin-film structures is studied using numerical methods. The obtained results suggest that it should be possible to obtain optically induced increase in current density of the order of 107 in modified thin film structures as a result of deliberate modification of trap density at the emitter consisting in formation of high density of traps at the emitter.

Badane są metodami numerycznymi prądy ograniczone ładunkiem przestrzennym w świadomie modyfikowanych strukturach cienkowarstwowych. Otrzymane wyniki sugerują, że powinno być możliwe uzyskanie optycznie indukowanego wzrostu gęstości prądu rzędu 107 w układach z modyfikacją koncentracji pułapek przy emiterze, polegającą na wytworzeniu cienkiej warstwy o dużej koncentracji pułapek.
Fotowzmocnione przewodnictwo w niejednorodnych układach cienkowarstwowych zdominowanych przez prądy ograniczone ładunkiem przestrzennym.
Institute of Physics, Faculty of Technical Physics, Information Technology and Applied Mathematics. Lodz University of Technology
Instytut Fizyki, Wydział Fizyki Technicznej, Informatyki i Matematyki Stosowanej, Politechnika Łódzka
Keywords: space charge limited currents; optical switching; prądy ograniczone ładunkiem przestrzennym; struktury cienkowarstwowe; gęstość prądu